Effect of aqueous extract of chañar (Geoffroea decorticans Burkart) on Botrytis cinerea, as possible alternative for control in post-harvest of table grape - Boiteux, Joana Jaqueline; Hapon, María Vanda; Fernández, María de los Ángeles; Lucero, Gabriela Susana; Pizzuolo, Pablo Humberto (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2015)
Botrytis cinerea is a parasite fungus that causes destructive diseases over several crops and important economic damages. In grapes causes berry softy rots, which decreases both harvest yield and grape, must and wine quality. In order to ensure quality, different controls are used, such as cultural measure and fungicide applications. Last one, presents adverse effects in environment and its residue affect human health. Plant extracts are a valid alternative method. The objectives of this study were to determine the biological effect of aqueous extract of Geoffroea decorticans (chañar) on germination and germ tube growth of conidia of B. cinerea and to determine its efficiency in vivo control. To accomplish the objectives different concentrations of plant extract were tested over conidia of the pathogen. Efficiency of in vivo control on bunches of grapes cv. Red Globe was determined for different concentrations of plant extract. Also, control efficiency was compared with the chemical controls dicloran and sulfur dioxide. From these studies it was determined that the chañar extract inhibited germination and germ tube growth of conidia of B. cinerea. In vivo tests, under preventive treatments with chañar extract showed that the percentage of diseases berries decreases.